Pengembangan E-LKPD Fluida Statis Berbasis Model Learning Cycle 7E Menggunakan Aplikasi Canva: Development of Static Fluid E-LKPD Based on the 7E Learning Cycle Model Using the Canva Application - Erni Kusrini Sitinjak; Juliaster Marbun; Irving Josafat Alexander; Irmadayanti Sagala (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
E-LKPD is a medium students can use to train themselves and hone their ability to master a learning material. As a training medium, E-LKPD is one of the evaluation tools that can be used to measure student achievement in the learning process. For this reason, the compiled E-LKPD should pay attention to the elements of student characteristics and learning conditions. This research was conducted at SMA Swasta Bersama Berastagi. This type of research is Research and Development (R&D) using the ADDIE model with the stages of Analysis, Design, Development, Implementation, and Evaluation. The data used in this study are test data on learning outcomes for understanding concepts using the compiled E-LKPD and questionnaire data from distributing questionnaires to measure student enthusiasm in learning. The subjects in this study were 35 students of class X SMA Swasta Bersama Berastagi. E-LKPD was designed interactively with the Canva application and validated by experts with 2% and 87%. Scores The SMA Swasta Bersama Berastagi trial showed a significant increase in student scores, from an average of 60.25 to 79.85 after using E-LKPD. Students also responded positively through questionnaires, showing increased motivation, engagement, and understanding. These results prove the effectiveness of E-LKPD in improving the quality of learning and are recommended for application to other materials. This study uses the ADDIE model to develop interactive E-LKPD to enhance students' understanding of static fluids. The results showed a significant increase in students' average scores after using E-LKPD. In addition, students felt more interested and active in learning, indicating the effectiveness of this learning media.